The Association Between Human Cytomegalovirus and Salivary Gland Cancer: An Analytical Study and Literature Review - Hagir Abd Rahman Mahmoud; Ahmed Mohamed Suleiman; Elwaleed Mohamed Elamin; Sawsan Abdel Rahim Mohammed (Sudan Journal of Medical Sciences)
Background: Human cytomegalovirus (HCMV) is a widespread human pathogen that triggers varying clinical symptoms depending on the host’s age and immune status. It appears that HCMV infection plays a role in the development of numerous types of cancer. This study aimed to identify the presence of HCMV in different kinds of malignant salivary gland tumors in Sudanese patients. Methods: Eighty-four formalin-fixed paraffin-embedded tissues (FFPE) from Sudanese patients previously diagnosed with salivary gland cancer (SGC) between 2014 and 2022 were selected. All cases include normal salivary gland tissue. Immunohistochemical staining for CMV was performed using monoclonal antibodies to detect the presence of the virus among the studied group. Results: CMV was detected in only 1 out of 84 SGC cases; an adenoid cystic carcinoma. All adjacent normal salivary gland tissues were negative for the virus. Conclusion: The absence of CMV in the studied cases suggests that the virus was not involved in developing these malignancies.